Carceral reckoning and twenty-first century US abolition movements: Generational struggles in the fight against prisons - Kurti, Zhandarka (Punishment & society, 2023)
The spectacle of racist state violence in the middle of a global pandemic was the spark that ignited one of the largest Black led and multiracial protest movements in recent history. The George Floyd rebellion propelled abolitionist politics from the margins to the mainstream of American political life. In the span of a few months, abolitionism supplanted liberal visions of reforming the carceral state. While important academic work continues to highlight the social and historical context that produced such widespread resistance to the American punishment regime, very little attention has been paid to how and why abolitionism gained such mainstream acceptance. We argue that the successful mainstreaming of the twenty-first century abolitionist response to the crisis of the carceral state is due to generational and intergenerational experiences of mostly Black and Brown organizers fighting against policing and incarceration. As new abolitionism forces reckonings with the carceral state and its major institutions, through important shifts, methodologies, and newly imagined forms of freedom, these movements necessitate new questions in the study of punishment: What are the tensions and contradictions that twenty-first century abolitionists are contending with as they build intergenerational movements against policing and prisons? How does the abolitionist legacy inform the work that we do as scholars and activists? How does the carceral reckoning realign political education and struggle?